Farmers’ Perception on Dodder (Cuscuta Spp) Parasitic Plant in Uasin Gishu County, Kenya - Kokwon, C.; Ngode, L.; Chepkoech, E.; Oimbo, L. M.; Alkamoi, B. M. (Africa Environmental Review Journal, 2022)
Dodder plant is an annual holoparastic plant, widely distributed and colonizing diversity of habitats. It is an invasive weed that causes ecological and economic damage to crop production and biodiversity. Its massive invasion causes a lot of panic to farmers as it may lead to total crop failure and degradation of forests with little information known about it. The study aimed at determining the farmers’ knowledge, attitudes and practices on dodder plant in Uasin Gishu County for the purpose of coming up with strategies to cope with the menace. A survey study was done in all the sub counties within the county to ascertain the trend of the parasitic weed. Stratified, Purposive and convenient sampling were used to collect data from 384 farmers in the County. Data was analyzed both qualitatively and quantitatively. Descriptive statistics was employed. From the results, most of the respondents (98%) were aware of dodder plant though most of them (76 %) did not have a local name of referring the weed. Also 40% of the respondents had their farms invaded by the weed while 60% did not, citing that the weed was a mysterious plant and that it was spotted in the area less than 5 years ago (64%). Children play a significant role in its dispersal (41%). Most of the respondents could do nothing about the weed (57%) though they could only try to control it manually (40%) as they could not understand it. Therefore, there is need by the stakeholders to intensify awareness among the locals, including use of media to reach wider audience on the dangers of dodder weed to food security, biodiversity and their livelihoods and encourage collaboration with other relevant Institutions to better understand dodder and devise mechanisms to control and manage it.